Article Withdrawal by ASERS Publishing - Fraudulent double submission and legal limitations - Spatial Tourism Planning: Using the Model of Functional and Planning Complexes - DUNETS, Alexandr; MUHAMEDIEVA, Ardak; SYCHEVA, Irina; PEREPECHKINA, Elena; VAKHRUSHEV, Igor; KULCHYTSKIY, Aleksey (Journal of Environmental Management and Tourism; Vol 10 No 4 (2019): JEMT Volume X Issue 4(36) Summer 2019DO - 10.14505//jemt.v10.4(36).01, 2019)
The article examines the problem of spatial tourism planning. The authors note that the possibility of tourist activities in different territorial zones requires functional zoning. The study justifies the use of a territorial tourist complex concept. The authors propose using the model of functional and planning complexes as a basis for understanding the structure of the territorial tourist complex, as well in the spatial development of tourism. Spatial planning of tourism implements various approaches. However, the main problem of the territorial tourist complexes’ development arises because tourist activity can be carried out in the territories of various purposes. Multi-functional zones are important for tourism as this determines their specialization and tourist flows. The study of territorial tourist complexes is related to the problem of using this concept in the practice of spatial development. Therefore, an urgent task is to develop a model that characterizes the structure of the tourist complex, which will enable moving on to an understanding of tourism development planning.